SECURITIZATION IN THE CONTEXT OF ELECTIONS - UKRAINIAN WAR AND SERBIAN 2022 ELECTION CAMPAIGN - Nedic, Pavle (Political Review, 2023)
The Ukrainian war, which began on February 24 2022, with the entry of Russian troops into the territory of the aforementioned country, represents the first war between two sovereign states on the European continent in the 21st century. This conflict caused dramatic disruptions in many aspects. In addition to reopening the issue of military security on European soil, Russia’s position as one of the key exporters in the energy market, as well as the importance of Russia and Ukraine in the food market, this war has led to additional crises at the international level which required strategic adjustments by other European countries, including Serbia. The war in Ukraine coincided with the election campaign for the presidential and parliamentary elections in Serbia, which took place on April 3, 2022. The paper starts from the research question of how electoral actors in the 2022 election campaign in Serbia securitized the war in Ukraine. Securitization of a certain issue implies its displacement from the political to the security sphere. Securitization is performed by securitizing actors with a specific speech act directed towards a specific audience. The goal of securitization is to gain support for the introduction of special measures that would adequately respond to the securitized issue. The authors introduce a special category of securitization in elections, more specifically during elections campaign, which represents a special political context that shapes the process of securitization through several factors. Using this framework, the authors hypothesize that in the election campaign in Serbia there were three approaches of electoral actors towards the securitization of the war in Ukraine, which were formed on the basis of their political positioning and ideology.